Penyuluhan Kesehatan Reproduksi Pada Remaja: Reproductive Health Education for Adolescents - Narti, Samsi; Rufaridah, Anne; Dahlan, Asmita; Komalasari , Wuri; Husni, Lailatul; Nasution, Lisna Khairani (Chakra Brahmanda Lentera Institute, 2024)
The young generation is the fate of the nation where they can do something useful for the country, but if people who are mature 10-24 years old do not progress as they should, the nation will experience a loss of age and it is estimated that in 2020 to 2030 it will become a big issue. for this country due to its ever-increasing population and uncontrolled sexual mentality, the younger generation is ignorant about conceptual well-being. This activity method is reproductive health education for teenagers in one meeting. There were 30 teenagers taking part in counseling activities. The media used were leaflets, infocus, laptops and hand points. As a result of community service, 60% of respondents were able to answer questions about reproductive health in adolescents. Apart from that, participants also participated in asking questions about the material. Considering the various issues related to reproductive health in adolescents, it is important to provide reproductive health education for adolescents through counseling so that they can receive correct and accurate knowledge information regarding reproductive health and can go through puberty well and avoid risky behavior in the Kubu Dalam sub-district Parak Karakah.